Effect of different intracanal medicaments combined with chitosan nanoparticles on microhardness and fracture resistance of root dentin - An in vitro study - Rahul Halkai; Kiran R. Halkai; Syeda Uzma Mahveen (Wolters Kluwer Medknow Publications, 2024)
Introduction: Chitosan nanoparticles (CSN) are widely used for endodontic disinfection; however, their combination with other intracanal medicaments is least studied; therefore, this study aims to evaluate the effect of various intracanal medicaments incorporated with 0.2% CSN on root dentin microhardness and fracture resistance. Materials and Methods: Fifty extracted human single-rooted premolars were cleaned, decoronated, and standardized to 13 mm root length. After access opening and working length determination, specimens were instrumented with ProTaper rotary files till apical size F3 and alternatively irrigated with 5 ml of 2.5% sodium hypochlorite and normal saline (NS). Final irrigation was done with 5 ml of 1% phytic acid. The specimens were allocated randomly into five groups (n = 10), followed by placement of intracanal medicament for 1 week as follows. Group 1 - 0.2% CSN, Group 2 - Calcium hydroxide (Ca[OH] 2) + 0.2% CSN, Group 3 - Triple antibiotic paste (TAP) + 0.2% CSN, Group 4 - Propolis + 0.2% CSN, and Group 5 - Chlorhexidine gluconate (CHX) + 0.2% CSN. The specimens were then rinsed with NS and 3 mm coronal portion of each specimen was horizontally sectioned to create dentin blocks that were further split vertically and tested for Vickers microhardness (n = 10). The remaining root segment of each specimen was then vertically embedded in an acrylic block and evaluated for fracture resistance (n = 10) under a universal testing machine. The data acquired were statistically assessed using one-way ANOVA and posthoc Tukey tests (P < 0.05). Results: Propolis incorporated with 0.2% CSN showed the highest microhardness and fracture resistance values followed by CHX + 0.2% CSN, TAP + 0.2% CSN, Ca(OH)2 + 0.2% CSN, and least in 0.2% CSN alone. Conclusion: Intracanal medicaments incorporated with 0.2% CSN exhibited a synergetic effect on microhardness and fracture resistance of endodontically treated teeth; however, propolis with 0.2% CSN exhibited higher microhardness and fracture resistance of root dentin.